Los juegos libres y el desarrollo de la creatividad en niños de la Institución Educativa Inicial N° 313 Cuna Jardín, Iquitos 2022 - Flores Mori, Monica Nohelia (2024)
The purpose of the study was to relate free games and the development of creativity in children of the Initial Educational Institution No. 313 Cuna Jardín, Iquitos, 2022, with a relational methodology, the study design was non experimental, the sample of 135 children selected by the non-probabilistic method. The results when relating free games and the development of creativity in children determined that creativity develops whenever free games are developed, as demonstrated by the Kendall Taub statistic for ordinal variables whose calculated value was 0,188; p-value=0,004 (p<0,05), when describing whether children develop free games, it was observed that 93,3% of children always developed free games, knowing the level of creativity it was determined that 92,6% of children develop creativity, by associating free games and the development of creativity in children, from the analysis of the hypothesis test, the statistical value of the Spearman's Rho correlation coefficient = 0,756 was obtained, p-value equal to 0,000 being p<0,05, with which Ho is rejected and Ha is accepted, which demonstrates a high positive relationship. It concludes that free games are positively related to the development of creativity in boys and girls from the initial educational institution Cuna Jardín N°313, Iquitos, 2022.